TUMORAL EXTRAMEDULLARY HEMATOPOIESIS IN MEDISTINUM - CASE REPORT AND REVIEW OF RELEVANT DOCUMENTATION (Tạp chí Y học Cộng đồng, 2022)
Extramedullary Hematopoiesis (EMH) is the expansion of stem cells, hematopoieticprogenitor cells and their differentiation outside the bone marrow. This condition occursas a compensatory mechanism for the ineffective hematopoiesis of the bone marrow.Pathological EMH is triggered by hematopoietic disorders and other pathologicalstress conditions, such as infections, malignant tumor, anemia, and metabolicdisorders. Pathological EMH has been reported to occur in many organs, and sitesof pathological EMH may be involved in reactivation of embryonic hematopoieticstructures in these organs. Pathological EMH has been extensively studied in recentyears. In particular, pathological EMH caused by end-stage malignancy contributesto tumor immunosuppression. Thus, a deeper understanding of the mechanism ofpathological EMH could be beneficial for the development of therapies against tumordevelopment processes.We report a rare case of an extramedullary hematopoietic tumor in the mediastinum,diagnosed by histopathology, for reference to colleagues.
Keywords: Extramedullary Hematopoiesis; Tumoral extramedullary hematopoiesis, Cytology; Histopathology.